Analisis Faktor - Faktor Yang Memengaruhi Penggunaan Smartphone Dengan Menggunakan Metode Structural Equation Modeling (SEM) - Nungki Dwi Prastanti; Ari Kusyanti; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Smartphone is an internet-enabled phone which provides a Personal Digital Assistant (PDA) functions such as a calendar, calculator, address book, diary, and notes. In addition, smartphone also defined as one of the technological evolution in the form of devices to meet the desires of its users. Smartphone technology has been adopted by many industrial sectors, such as, banks, health care, food, transportation which will improve user experience toward new technologies. Smartphones become one of the important things and desperately needed by Indonesian people at this moment. Using the smartphone, variety of work can be done more easily, faster and certainly more practical. Many benefits to be gained from the use of smartphone. That is encourage people to buy and use a smartphone. The desire to use a smartphone is influenced by various factors. This study aims to identify factors that affect the use of smartphones by using eight variables constructs. Data were collected by distributing online questionnaires to 248 smartphone users. Structural Equation Modeling (SEM) is used as data analysis method. From the analysis process using Structural Equation Modeling (SEM) can be concluded that the research model has a good fit level with research data because the test results show if the value of Goodness of Fit Indieces have met the criteria. In addition, the result of this study indicates that the factors which have positive affect toward Behavioral Intention to use smartphone that will affect the variable actual use of smartphone are Perceived Usefulness, Perceived Ease of Use, and Perceived Trust.